PENGARUH KEBIASAAN DAN SIKAP BELAJAR TERHADAP PRESTASI BELAJAR MATA PELAJARAN EKONOMI PADA SISWA KELAS XII IPS DI SMA NEGERI 7 PEKANBARU T.A 2018/2019 - Putri, Indah Permatasari; Gimin, Gimin; Suarman, Suarman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study aims to determine the effect of Habits and Attitudes of Learning on Learning Achievements in Economic Subjects in Class XII IPS Students at Pekanbaru 7 High School T.A 2018/2019. This research is descriptive quantitative using a correlational approach. The population in this study were all students of class XII IPS in Pekanbaru T.A 2018/2019 Public High School 7 consisting of 4 classes totaling 150 students and a sample of 110 students using simple random sampling technique. This study uses multiple linear regression techniques using the t test, F test and to determine the percentage influence of Habit and Learning Attitudes toward Learning Achievement using the coefficient of determination (R2). Based on the results of the study of Student Learning Habits at Pekanbaru 7 High School included in the Good category, the Learning Attitude of students in Pekanbaru 7 High School is also included in the Good category. From the data analysis it was found that student learning habits significantly influence learning achievement, student learning attitudes also have a significant influence on learning achievement. Simultaneously it turns out that Student Learning Habits and Attitudes significantly influence Learning Achievement with a coefficient of determination (R2) of 48.2% while the remaining 51.8% is determined by factors such as learning motivation, learning discipline and so on. For students to increase the habit of doing economic assignments both at home and at school, individual assignments and group assignments. As well as being more good towards Economics and other lessons. Because by practicing getting used to making assignments well, coupled with a good attitude towards the lessons learned is believed to be able to make learning achievements better and keep increasing.Keyword: Learning Habits, Learning Attitudes, Learning Achievements.